Pendampingan Perangkat Desa melalui Smart Village di Desa Tepusen Kec Kaloran Kab Temanggung - Husein Mahmud; Salis Irvan Fuadi; Hierro Chosha Putro; M.Ghufron; Maulina Amany; Shehah Nadhifatus Sayyida; Afna Azam Firdaus; Cesaria Rindu Dara; Ahmad Zainun; Uswatun Khasanah; Ipang Mei Esajati Dwi Angga; Yoga Ari Cahyadi; Eka Putri Savarita; Istiqomah Istiqomah; Muhammad Khoidar Atho (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research explores the application of the Smart Village concept in Tepusen Village, Kaloran District, Temanggung Regency. In the digital era, villages are expected to utilize technology to improve the quality of public services and community participation. This research aims to: 1) Understanding Smart Village and Village Technology Infrastructure Readiness; 2) Role and Involvement of Village Apparatus; 3) Public Services and Village Management; 4) Challenges and Solutions. This study uses a qualitative method with a case study approach, involving interviews and observations of village officials and communities. The results of the study show that the application of information and communication technology in Tepusen Village has improved administrative efficiency and service transparency. Despite challenges such as low digital literacy among the community, collaboration between village officials and KPM students provides a significant solution to overcome these obstacles. These findings show the importance of government support and active community participation in realizing inclusive and competitive smart villages.